ORGANIZATIONAL AND COMMUNICATION SUPPORT OF THE PROCESS OF DECISION MAKING IN THE EDUCATIONAL SPHERE - Olga Verdenhofa; Jevgenija Dehtjare; Oleksiy Dzenis; Roman Djakons; Julija Mironova (International Comparative Jurisprudence, 2022)
This article examines the essence of the definitions of management decision and decision-making, highlighting the essential components of these definitions. This later allows us to provide the authors’ definition of the concept of organizational and communication support of the decision-making process in the educational sphere. The article analyzes decision-making models that can be extrapolated in educational institutions under reform conditions. The Rational model is highlighted as a priority decision-making model for the educational sphere. Unlike existing models, the Rational model differs in a significant number of economic criteria, which helps to make accurate decisions among existing alternative choices. The communication process is considered, taking into account the stages of decision-making, where the relationships and correlations between actions at each stage of decision-making are revealed. This subsequently makes it possible to form a matrix of the interrelationship of factors of the development of organizational and communication support and stages of decision-making. The study of organizational and communication support for the decision-making process in higher education institutions makes it possible to schematically depict a complex organizational structure, where close communication links between departments are defined. It is noted that nformation about decisions is mainly provided remotely through the internal module of information and communication support. This allows the administrative and management unit to distribute management information for execution simultaneously to all units, eliminating the distortion of information. It also enables the educational institution to effectively interact with the external environment. The selected components of the organizational and communication support of the decision-making process allow a comprehensive approach to the substantiation of the hypothesis, which is based on the perception of organizational and communication support as necessary tools that have an impact on the quality of the decision-making process in the educational sphere.